Corporate tax avoidance: a crime of globalization - Evertsson, Nubia (Crime, law and social change, 2016)
This article approaches tax avoidance as a crime of globalization. Tax avoidance is not just a problem originating in the corporation. Corporate tax avoidance is a practice that involves different corporations and different territories simultaneously and, as such, it has global consequences because these corporations do not pay their fair tax in the countries in which they operate. As it is seen here, the free-market creates opportunities for tax avoidance when nations and territories strive to attract international investment by changing their tax rules in favor of powerful corporations. Tax regulations have been re-written by tax authorities, financial controls have been removed, and secrecy has been guaranteed to provide a favorable atmosphere for investors. However, tax authorities only give total exemptions to foreign and non-domiciled corporations while taking taxes from their own citizens and national corporations. In all, the tax incentives offered are not the result of less state intervention in the economy but are instead the product of more state intervention in rewriting the rules of the economy in favor of the powerful.